From waste to energy: a techno-economic analysis and life cycle analysis of liquid biochemical production from wet wastes through enhanced anaerobic digestion - Soliman, Abdallah, author; Quinn, Jason C., advisor; Reardon, Kenneth, committee member; Windom, Bret, committee member (Colorado State University. Libraries, 2022)
Wet wastes such as manure and food wastes present problems due to disposal costs and environmental impacts. Low value products and methane leaks limit the sustainability and viability of current anaerobic digestion for treatment of wet waste. Electrochemically enhanced conversion of wet wastes diverts carbon from low-value methane into volatile fatty acids that are subsequently upgraded to improve anaerobic digestion sustainability and generate biochemicals which are seamlessly compatible with the current infrastructure. A chain elongation pathway and a bioconversion pathway are used to produce caproic acid and n-butanol, respectively. Techno-economic analysis and life cycle assessment are used to demonstrate the economic and environmental viability of the technology. The economic analysis generates market competitive minimum selling prices of $1.05 per kg for the caproic acid pathway and $2.25 per kg for the n-butanol pathway. The baseline environmental analysis yields an environmentally unfavorable GWP of 72.1 g CO2-eq·MJcaproic acid-1 for the chain elongation pathway whereas the GWP of the bioconversion pathway (24.0 g CO2-eq·MJn-butanol-1) qualifies it as a renewable fuel under the RFS program. Using scenario and sensitivity analyses, critical research areas were highlighted to guide future work and improve the performance and sustainability of the technology.
Keywords: caproic acid; food waste; Monte Carlo; environmental analysis; butanol; manure